Small and Isolated Immunohistochemistry-positive Cells in Melanoma Sentinel Lymph Nodes Are Associated With Disease-specific and Recurrence-free Survival Comparable to that of Sentinel Lymph Nodes Negative for Melanoma. (June 2019) - LeBlanc, Robert E.; Barton, Dorothea T.; Li, Zhongze; Angeles, Christina V.; Ernstoff, Marc S.; Bagley, Eryn; Wimmer, Daniel; Wong, Sandra L.; Barth, Richard J.; Shirai, Keisuke; Yan, Shaofeng
Abstract : Although immunohistochemistry (IHC) has improved our ability to detect melanoma metastases in sentinel lymph nodes (SLN), the American Joint Committee on Cancer (AJCC) does not provide a lower threshold for determining if a SLN is positive for metastasis. Existing literature suggests that even a small aggregate or an enlarged, abnormal cell detectable by IHC can be associated with an adverse outcome. In our experience, however, some SLNs contain small solitary cells the size of neighboring lymphocytes demonstrable only by IHC. We sought to determine their clinical significance. A total of 821 patients underwent a SLN biopsy at our institution over a 12-year period. In all, 639 (77.8%) were SLN-negative, 125 (15.2%) were SLN-positive, and 57 (6.9%) had rare IHC-positive cells of undetermined clinical significance with no disease progression over a mean 59-month follow-up. Kaplan-Meier method with pair-wise comparisons revealed no significant difference in disease-specific survival and recurrence-free survival between SLN-negative and rare IHC-positive groups. There were significant differences in survival and recurrence between patients in the rare IHC-positive group and those with melanoma metastases, including those with solitary melanoma cells and those with tumor burdens ⩽0.2 mm. While the lower diagnostic threshold for metastatic melanoma on IHC-stained sections needs to be studied further, our data suggest that rare IHC-positive cells lacking cytomorphologic features of overt malignancy are equivocal for melanoma and could impart a similar prognosis as patients with no evidence of SLN involvement.